Acute aortic dissection in a patient with Williams syndrome infected by COVID-19. (12th January 2021) - Mamishi, Setareh; Navaeian, Ameneh; Shabanian, Reza
Abstract: Cardiovascular involvement in COVID-19 has different features. Here we report the ominous fate of a neglected adolescent with Williams syndrome that was infected by SARS-CoV-2 and ended by acute aortic dissection.